Process evaluation of Tuberculosis infection control and prevention practice at public health facilities in Tegede district, Northwest Ethiopia: Facility-based cross-sectional design. - Endalkachew Mesfin Gebeyehu; Ashagere Mebratu; Asmamaw Atnafu; Asebe Hagos (PLoS ONE)
Background Tuberculosis Infection Prevention and Control practice (TB-IPC) is crucial to prevent nosocomial transmission of Tuberculosis (TB), especially in high-burden settings like Ethiopia. However, studies show that TB infection control practices among healthcare workers in Ethiopia are suboptimal. The study aims to evaluate TB-IPC practices at public health facilities in Tegede district, Northwest Ethiopia. Methods A facility-based cross-sectional design with mixed methods and a formative approach was used to evaluate the TB-IPC from May 1 to June 30, 2023. The practice was assessed using availability, compliance, and acceptability dimensions with 31 indicators. The quantitative data was collected from 525 clients using structured questionnaires. The data were coded, entered into EpiData version 4.6, and exported to SPSS version 25 for analysis. Binary and multivariable logistic regression analyses were used to identify the predictor variables associated with client satisfaction. Furthermore, non-participatory direct observations, document reviews, and resource inventories were conducted. In the qualitative study, key informants were interviewed, and qualitative data were transcribed, translated, coded, and analyzed manually in themes. Result The overall implementation of TB-IPC practice was 54.4%. The availability dimension was 50.4%, compliance was 67.2%, and acceptability was 43.4%. A total of 525 clients participated, with a response rate of 96.2%. In the multivariable logistic regression analysis, occupation was the predicator variable with a p-value of <0.05. In total, 134 (25.5%) clients, with a 95% CI [22.0%, 29.4%], were satisfied with TB-IPC practices at public health centers in Tegede district. Conclusion The overall implementation of TB-IPC practices at public health facilities in Tegede district is currently poor and requires urgent improvement. Based on stakeholders' judgment criteria, the dimensions of availability, compliance, and acceptability were rated as poor, fair, and poor, respectively. These findings provide a baseline understanding of how TB-IPC practices are implemented in Tegede district.